2019
DOI: 10.1371/journal.ppat.1007671
|View full text |Cite
|
Sign up to set email alerts
|

Fimbriae reprogram host gene expression – Divergent effects of P and type 1 fimbriae

Abstract: Pathogens rely on a complex virulence gene repertoire to successfully attack their hosts. We were therefore surprised to find that a single fimbrial gene reconstitution can return the virulence-attenuated commensal strain Escherichia coli 83972 to virulence, defined by a disease phenotype in human hosts. E . coli 83972 pap stably reprogrammed host gene expression, by activating an acute pyelonephritis-associated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 69 publications
(87 reference statements)
3
35
0
Order By: Relevance
“…The gene papGII has been associated epidemiologically with pyelonephritis and urinary-source bacteremia in directed, usually PCR-based studies [19][20][21][22]47 , and was shown experimentally, with varying degrees of rigor, to contribute to kidney infection in murine and monkey models [48][49][50] . A key role for papGII in the pathogenesis of human pyelonephritis was confirmed recently by the finding that knock-in of papGII was sufficient to enable the iuc-positive but normally non-pathogenic E. coli strain ABU83972 (CC73, phylogroup B2) to cause pyelonephritis in humans 23 . In that study, PapGII was shown to enter kidney cells and to trigger renal tissue inflammation by reprogramming host gene expression 23 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The gene papGII has been associated epidemiologically with pyelonephritis and urinary-source bacteremia in directed, usually PCR-based studies [19][20][21][22]47 , and was shown experimentally, with varying degrees of rigor, to contribute to kidney infection in murine and monkey models [48][49][50] . A key role for papGII in the pathogenesis of human pyelonephritis was confirmed recently by the finding that knock-in of papGII was sufficient to enable the iuc-positive but normally non-pathogenic E. coli strain ABU83972 (CC73, phylogroup B2) to cause pyelonephritis in humans 23 . In that study, PapGII was shown to enter kidney cells and to trigger renal tissue inflammation by reprogramming host gene expression 23 .…”
Section: Discussionmentioning
confidence: 93%
“…A key role for papGII in the pathogenesis of human pyelonephritis was confirmed recently by the finding that knock-in of papGII was sufficient to enable the iuc -positive but normally non-pathogenic E. coli strain ABU83972 (CC73, phylogroup B2) to cause pyelonephritis in humans 23 . In that study, PapGII was shown to enter kidney cells and to trigger renal tissue inflammation by reprogramming host gene expression 23 . These findings, together with ours, support a site (i.e., kidney)-specific and, hence, pathotype-defining role for papGII .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the addition of a single virulence gene to E. coli 83972 was sufficient to override the inhibitory effect of NlpD (50), bypassing Pol II inhibition at the transcriptional level. The calm, non-reactive environment created by commensals thus appears to be favored but easily disrupted if the strain acquires a sufficiently potent virulence gene (50).…”
Section: Discussionmentioning
confidence: 99%
“…3 ; Table 1 ). Importantly, bacteria that express TLR4 agonists, such as P fimbriae, can override this unresponsiveness by engaging different TLR4 coreceptors, such as glycosphingolipids 79 . This mechanism provides mucosal membranes with a much needed, pathogen-specific solution for when to respond to bacteria in the lumen.…”
Section: Asymptomatic Bacteriuriamentioning
confidence: 99%